Hope After Cancer: Pregnancy Outcomes Following Fertility-Sparing Surgery – A Case Report - Marpaung, Richardo; Armanza, Ferry; Yuseran, Hariadi; Waluyo, Setyo Teguh; Salan, Yosef Dwi Cahyadi (Heca Sentra Analitika, 2025)
Pregnancy after diagnosis of ovarian cancer is a rare event. Ovarian Cancer is associated with difficulty in achieving pregnancy. Little is known about the mechanism of this condition due to limited literature and studies. In this paper, the authors report a rare case of successful pregnancy in a patient with ovarian cancer. Patient initially diagnosed with cystadenocarcinoma mucinous of the ovary, two years prior to pregnancy, and later diagnosed with suspected ovarian cancer in the third trimester. The patient was then treated with optimal debulking surgery and cesarean section at 35 weeks of pregnancy. The patient delivered a healthy baby girl. Debulking surgery was carried out, and the patient was scheduled for chemotherapy. The findings from this case conclude that patients with ovarian cancer who receive conservative surgical treatment could have successful pregnancy outcomes. The quality of the patient’s life should be a priority, and follow-up for further treatment is essential.